Cobalt-containing hexagonal mesoporous molecular sieves (Co-HMS): Synthesis, characterization and catalytic activity in the oxidation reaction of ethylbenzene - Bhoware, Shrikant S.; Shylesh, S.; Kamble, K. R.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2006)
Cobalt-containing hexagonal mesoporous materials (Co-HMS and Co/HMS) with different cobalt content were synthesized for the first time by direct hydrothermal and post-synthesis (grafting) method. The materials were characterized in detail by X-ray diffraction, BET surface area, N-2 sorption isotherms, SEM, TEM, UV-vis and XPS techniques. Powder X-ray diffraction pattern, N2 adsorption-desorption analysis and TEM analysis show the presence of hexagonal mesoporous structure, having Type W isotherms and reveals the typical wormhole-like morphology. Spectroscopic techniques like UV-vis and XPS reveal cobalt in +2 oxidation state and tetrahedrally coordinated. Liquid phase oxidation of ethylbenzene using TBHP (70 wt%) as an oxidant shows that the catalysts are highly active, under solvent free conditions as well as under lower cobalt concentrations. Leaching studies performed by hot filtration experiments show that the cobalt catalysts prepared by hydrothermal methods are stable, while the grafted catalysts show the leaching of cobalt under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Co-HMS; ethylbenzene; HMS; hydrothermal; Oxidation

Catalytic activity of cobalt containing MCM-41 and HMS in liquid phase oxidation of diphenylmethane - Bhoware, Shrikant S.; Kamble, K. R.; Singh, A. P. (Catalysis Letters, 2009)
Cobalt containing MCM-41 and HMS were synthesized by direct hydrothermal (DHT) and post synthesis methods (grafting and immobilization). The catalytic activity of these materials was investigated in the liquid phase oxidation of diphenylmethane at 80 A degrees C with TBHP (70 wt%) as oxidant. Comparative study of cobalt containing MCM-41 and HMS was carried out to reveal the catalytic performance of framework, extraframework and immobilized cobalt species. The role of the solvent in the performance of catalyst was examined with different polar and non polar solvents. Oxidation of diphenylmethane in solvent free media (under similar reaction conditions) shows formation of hydroxy derivatives of benzophenone in addition to main product (benzophenone). Hundred percent selectivity to benzophenone was obtained when the reaction was carried out in solvent.
Keywords: diphenylmethane; HMS; Immobilization; MCM-41; XRD